2019
DOI: 10.4081/or.2019.8306
|View full text |Cite
|
Sign up to set email alerts
|

Can pharmacological and non-pharmacological sleep aids reduce post-operative pain and opioid usage? A review of the literature

Abstract: Sleep is important for our health and well-being and is especially pertinent to orthopedic surgery because it has been shown to play a role in pain tolerance. Knowing the benefits of sleep, one way to positively impact patients’ pain and recovery post-surgery is to encourage sleep. Zolpidem, a pharmacologic sleep aid, has been shown to decrease opioid consumption, reduce pain, and increase quality of life when briefly used after orthopedic procedures. Cognitive Behavioral Therapy for Insomnia (CBT-I), a nonpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A review of several small studies found that prescribing sleeping aids, like zolpidem, after surgery can reduce postoperative opioid use. 36 This finding highlights the importance of preoperative counseling about the appropriate use of opioids after surgery. Surgical pain optimization programs should consider including additional counseling about nonpharmacological and non-narcotic pharmacological measures to improve postoperative sleep.…”
Section: Discussionmentioning
confidence: 92%
“…A review of several small studies found that prescribing sleeping aids, like zolpidem, after surgery can reduce postoperative opioid use. 36 This finding highlights the importance of preoperative counseling about the appropriate use of opioids after surgery. Surgical pain optimization programs should consider including additional counseling about nonpharmacological and non-narcotic pharmacological measures to improve postoperative sleep.…”
Section: Discussionmentioning
confidence: 92%
“…Patients can be impaired the morning after taking these medications, and the medications can cause complex sleep-related behaviors such as somnambulism 42 . A review of z-drug use in the postoperative period highlighted a decrease in pain as well as decreased opioid use in several studies and demonstrated that cognitive behavioral therapy aided in sleep as much as pain management postoperatively 43 . Those authors warned against prolonged z-drug use because of the risk of health issues and emphasized that pharmacologic sleep aids do not induce natural sleep.…”
Section: Adverse Effects and Risksmentioning
confidence: 99%